2019
DOI: 10.1002/hipo.23145
|View full text |Cite|
|
Sign up to set email alerts
|

Neurons and networks in the entorhinal cortex: A reappraisal of the lateral and medial entorhinal subdivisions mediating parallel cortical pathways

Abstract: In this review, we aim to reappraise the organization of intrinsic and extrinsic networks of the entorhinal cortex with a focus on the concept of parallel cortical connectivity streams. The concept of two entorhinal areas, the lateral and medial entorhinal cortex, belonging to two parallel input–output streams mediating the encoding and storage of respectively what and where information hinges on the claim that a major component of their cortical connections is with the perirhinal cortex and postrhinal or para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
162
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(178 citation statements)
references
References 224 publications
13
162
0
3
Order By: Relevance
“…Indeed, such rules have been observed in several cases. For example, ENTm and ENTl L2 and L3 neurons mainly project into the hippocampus and within ENT, whereas ENT L5 neurons mainly mediate the output projections (Nilssen et al, 2019), Similarly for SUB, it has been shown that superficial neurons mainly project within HPF whereas deep-layer neurons have subiculo-fugal or subiculo-thalamic projections (Bienkowski et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, such rules have been observed in several cases. For example, ENTm and ENTl L2 and L3 neurons mainly project into the hippocampus and within ENT, whereas ENT L5 neurons mainly mediate the output projections (Nilssen et al, 2019), Similarly for SUB, it has been shown that superficial neurons mainly project within HPF whereas deep-layer neurons have subiculo-fugal or subiculo-thalamic projections (Bienkowski et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It will be of immense interest to examine the extent to which transcriptomic cell types are the nodes underlying specific connectional pathways and playing specific functional roles. For example, we hypothesize that the Calb1 + L3 ENTm cells and the Reln + L2 ENTm cells may contain the pyramidal and stellate grid cells, respectively, based on the expression of these known grid cell marker genes (Ferrante et al, 2017; Nilssen et al, 2019). In addition, it has been shown that dorsal and ventral parts of the hippocampal and subicular regions preferentially form their respective interconnected networks (Bienkowski et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, since subthreshold resonance is equivalent to a band‐pass filter of theta frequencies (Richardson, Brunel, & Hakim, ), stellate cells could directly develop the hexagonal grid cell pattern through Hebbian learning by listening to the phase‐distance relationship present in CA1. Principal cells in Layer II of medial entorhinal cortex (mECII) do not receive direct input from hippocampal areas, but rather receive relayed input from layer Vb pyramidal cells (LVP), which likewise receive feedback input from LIIS cells (Buetfering, Allen, & Monyer, ; Fuchs et al, ; Nilssen, Doan, Nigro, Ohara, & Witter, ; Witter, Doan, Jacobsen, Nilssen, & Ohara, ). In addition, pyramidal cells in mECII (LIIP) also exhibit triangular patterns, and communicate with LIIS cells via intermediary cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, since subthreshold resonance is equivalent to a band-pass filter of theta frequencies (Richardson et al, 2003), stellate cells could directly develop the hexagonal grid cell pattern through Hebbian learning by listening to the phase-distance relationship present in CA1. Principal cells in layer II of medial entorhinal cortex (mECII) do not receive direct input from hippocampal areas, but rather receive relayed input from layer Vb pyramidal cells (LVP), which likewise receive feedback input from LIIS cells (Witter et al, 2017;Fuchs et al, 2016;Nilssen et al, 2019;Buetfering et al, 2014). In addition, pyramidal cells in mECII (LIIP) also exhibit triangular patterns, and communicate with LIIS cells via intermediary cells.…”
Section: Discussionmentioning
confidence: 99%